2001
DOI: 10.1080/00016470152846600
|View full text |Cite
|
Sign up to set email alerts
|

Increased interleukin-6 in collected drainage blood after total knee arthroplasty: An association with febrile reactions during retransfusion

Abstract: Sell (2001) Increased interleukin-6 in collected drainage blood after total knee arthroplasty: An association with febrile reactions during retransfusion, Acta Orthopaedica Scandinavica, 72:3, 270-272,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 11 publications
1
34
0
5
Order By: Relevance
“…The purpose of a re-transfusion system of autologous blood from the wound is to reduce the need for homologous blood transfusion. Re-transfusion of autologous blood as well as transfusion of homologous blood may influence the patient's immune system [8]. The reported results of studies where postoperative wound drainage is not used, vary considerably.…”
mentioning
confidence: 81%
“…The purpose of a re-transfusion system of autologous blood from the wound is to reduce the need for homologous blood transfusion. Re-transfusion of autologous blood as well as transfusion of homologous blood may influence the patient's immune system [8]. The reported results of studies where postoperative wound drainage is not used, vary considerably.…”
mentioning
confidence: 81%
“…Although the washing procedure in our study reduced IL-6 concentrations by 89% in the liver resection group and by 62% in the aortic surgery group, IL-6 concentrations in the autologous RBC were still higher than those found in healthy subjects [13]. Retransfusion of drainage blood with IL-6 concentrations 60 times higher than those measured in our study did not result in febrile reactions in orthopedic patients [14]. In general, the CS eliminates inflammatory mediators through the washing process.…”
Section: Discussionmentioning
confidence: 53%
“…Several studies have demonstrated an increase in concentration of complement split products and cytokines levels such as C3a, SC5b, TNF-α, IL-1α, IL-1β, IL-6 and IL-8 in shed blood, but only elevated IL-6 in plasma following transfusion [18,19]. One of the most common side effects of autologous blood transfusion is febrile reaction and it has been found to be related to higher concentration of IL-6 in shed blood [20]. We did not find any such side effects with our study.…”
Section: Discussionmentioning
confidence: 99%